ETR : Redline Design / Muhammad Haziq Hazwan Musa ... [et al.] - Musa, Muhammad Haziq Hazwan; Junaidi, Noor Farah Adila; Sabri, Nur Nadirah; Mohamed Tahir, Nurul Hazie Sharmira (2019)
The Redline Design is a partnership business that focus on the design of T-shirt, fabric and jersey for all sizes in Selangor area especially in Bandar Sunway, Petaling Jaya. There are four partners which are Muhammad Haziq Hazwan Bin Musa, Noor Farah Adila Binti Junaidi, Nur Nadirah Binti Sabri and Nurul Hazie Sharmira Binti Mohamed Tahir. That corporate together to run this business. The business located at No.51, Jalan PJS 11/9, Bandar Sunway, 46150, Petaling Jaya, Selangor. This is a new store building that built at a strategic placed which is at the centre of Bandar Sunway, Petaling Jaya, Selangor. The partners choose this location because the majority of the population here are middle to high income. Not only that, the population here are is quite high and average of the lifestyle here more to clean environment and like to nature. The partners sure that with the business, it can make customer feel easy to design and buy our products.